2000
DOI: 10.1159/000018890
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Leiomyosarcoma of the Distal Duodenum

Abstract: Malignant tumors of the small intestine are rare. An uncommon finding of leiomyosarcoma located in the fourth part of the duodenum was diagnosed by gastrointestinal contrast studies, CT and angiography. Although malignant lesions of the small bowel are usually diagnosed late and thus are far advanced, curative resection was possible in our case. The location and histology of the tumor permitted a ‘pancreas-preserving segmental duodenectomy’. The operative approach and exposure using the Cattell maneuver is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…However, in principle the reconstruction of the gastrointestinal tract should be performed by end-to-end anastomosis whenever possible, and a blind sac should be avoided as much as possible to prevent the development of the blind sac syndrome. Orda et al [7] also reported a GIST in the fourth part of the duodenum similar to our case. They performed end-to-end anastomosis between the descending duodenum and the proximal jejunum after the maneuver by Cattel and Braasch [6].…”
Section: Discussionsupporting
confidence: 89%
“…However, in principle the reconstruction of the gastrointestinal tract should be performed by end-to-end anastomosis whenever possible, and a blind sac should be avoided as much as possible to prevent the development of the blind sac syndrome. Orda et al [7] also reported a GIST in the fourth part of the duodenum similar to our case. They performed end-to-end anastomosis between the descending duodenum and the proximal jejunum after the maneuver by Cattel and Braasch [6].…”
Section: Discussionsupporting
confidence: 89%
“…40 The reports of duodenal GISTs that have been resected completely with PSDD have shown freedom of recurrence at 12-156 months. 18,21,22,24 Tw o of our 4 patients with stromal tumours had incomplete resections, and each of them was submitted to radical radiotherapy thereafter. Three of the 4 are alive and well with no evidence of recurrence at 36, 120 and 179 months, while one died during radiotherapy secondary to dehiscence of an ileocolic anastomosis that had previously healed.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] For neoplasms that arise in the third and fourth parts of the duodenum (D 3 , D 4 ), a conservative duodenectomy that preserves the pancreas and papilla can provide adequate tumour clearance while avoiding the additional dissection and risk associated with the biliary and pancreatic anastomoses implicit in the common alternative PD (or PSTD). Other advantages of this procedure include a shorter operative time and the preservation of more normal anatomy and function allowing postoperative endoscopic surveillance.…”
mentioning
confidence: 99%
“…11 Previous authors have suggested that the optimal surgical treatment for DSTs may be a local resection, 12,13 a pancreaticoduodenectomy, 14,15 or a pancreas-sparing duodenectomy. 4,16 Different survival rates have been given reported for a local resection and a pancreaticoduodenectomy. Regardless of the presentation, the diseasespecifi c survival rates with malignant DSTs are 69% at 1 year, 38%-44% at 3 years, and 29%-35% at 5 years.…”
Section: Discussionmentioning
confidence: 99%